Linguistic Insecurity The Effect of Attitudes toward Language on Language Production. Flowers of Evil - Baron, Dennis E. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1976)
This paper, a small part of a larger project which explores the effects of linguistic insecurity on language production, discusses the negative attitudes toward language of some of the present-day "language elite"--those who take pleasure in or earn their livelihood by "Correcting every body else." Linguistic insecurity is, then, the feeling that many Americans have that their use of language is full of errors, unskillful, or gauche. Edwin Newman's attitudes toward contemporary language (basically, that America will be the death of the English language) are summarized. In addition, the results of a study documented in the "Harper Dictionary of Contemporary Usage" are described. In this study, 136 distinguished consultants on language usage (Isaac Asimov, Charles Kuralt, Peter Prescott, and others) took a yes/no stand on questions of usage and commented on their responses. (KS)
ERIC Note: Paper presented at the 1976 Annual Meeting of the Modern Language Association.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Language Attitudes; Language Research; Language Role; Language Skills; Language Usage; North American English; Speeches/Meeting Papers